The Link between miRNAs and PCKS9 in Atherosclerosis - Macvanin, Mirjana T.; Gluvic, Zoran M.; Klisic, Aleksandra N.; Manojlovic, Mia S.; Suri, Jasjit S.; Rizzo, Manfredi; Isenovic, Esma R. (Current Medicinal Chemistry, 2024)
Cardiovascular disease (CDV) represents the major cause of death globally. Atherosclerosis, as the primary cause of CVD, is a chronic immune-inflammatory disorder with complex multifactorial pathophysiology encompassing oxidative stress, enhanced immune-inflammatory cascade, endothelial dysfunction, and thrombosis. An initiating event in atherosclerosis is the subendothelial accumulation of low-density lipoprotein (LDL), followed by the localization of macrophages to fatty deposits on blood vessel walls, forming lipid-laden macrophages (foam cells) that secrete compounds involved in plaque formation. Given the fact that foam cells are one of the key culprits that underlie the pathophysiology of atherosclerosis, special attention has been paid to the investigation of the efficient therapeutic approach to overcome the dysregulation of metabolism of cholesterol in macrophages, decrease the foam cell formation and/or to force its degradation. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a secretory serine proteinase that has emerged as a significant regulator of the lipid metabolism pathway. PCSK9 activation leads to the degradation of LDL receptors (LDLRs), increasing LDL cholesterol (LDL-C) levels in the circulation. PCSK9 pathway dysregulation has been identified as one of the mechanisms involved in atherosclerosis. In addition, microRNAs (miRNAs) are investigated as important epigenetic factors in the pathophysiology of atherosclerosis and dysregulation of lipid metabolism. This review article summarizes the recent findings connecting the role of PCSK9 in atherosclerosis and the involvement of various miRNAs in regulating the expression of PCSK9-related genes. We also discuss PCSK9 pathway-targeting therapeutic interventions based on PCSK9 inhibition, and miRNA levels manipulation by therapeutic agents.
Keywords: Atherosclerosis